PW 0458 Injury treatments and outcomes in preschool children with autism spectrum disorder: case-control study. (November 2018) - DiGuiseppi, Carolyn; Sabourin, Katherine R; Levy, Susan; Soke, Gnakub N; Lee, Li-Ching; Wiggins, Lisa; Schieve, Laura A
Abstract : Evidence about injury outcomes in children with autism spectrum disorder (ASD) is limited. We compared injury treatments and outcomes in children with ASD versus typically-developing (TD) controls. Children aged 30–68 months were recruited from education and health providers and randomly sampled birth certificates. Cases were determined using established ASD-specific diagnostic instruments. Parent-reported injury treatments and outcomes in ASD cases (n=224) were compared to TD (n=267) controls, overall and stratified by intellectual disability (ID) and attention problems (Child Behavior Checklist score or prior diagnosis), adjusting for sociodemographic characteristics and maternal psychiatric conditions using logistic regression. Injury nature, region and mechanism were similar between groups. ASD and TD children had comparable receipt of emergency care (EC) and/or hospitalization (82.1 percent vs 81.6 percent, adjusted odds ratio [aOR]=0.88 [95 percent CI: 0.56, 1.39]) and medication (41.5 percent vs 46.1 percent, aOR=0.79 [0.47, 1.31]) but ASD children more often had surgery (14.7 percent vs 5.2 percent, aOR=2.62 [1.49, 4.61]). Results were equivalent in ASD children with and without ID. Compared to TD children, ASD cases with attention problems had similar odds of receiving EC/hospitalization (aOR=1.77 [0.78, 4.02]), whereas those without attention problems were less likely to receive EC/hospitalization (aOR=0.55 [0.37, 0.82]). Parent-reported long-term/significant behavior change post-injury was uncommon (ASD 5.4 percent vs TD 3.4 percent, aOR=1.21 [0.51, 2.86]) and did not vary by ID status or attention problems. Significant differences in injury treatment/management were observed in ASD versus TD children. Attention problems in ASD children might have influenced management: those without attention problems were significantly less likely than TD children to have injury-related EC/hospitalization, a difference not observed for those with attention problems. Injuries rarely resulted in long-term or significant behavior change in children with ASD. Future research could explore differences in injury management in children with developmental delays/disorders, including ASD, and attention problems.